Traditional Arts of the Rancher and Cowboy - Laurie Hamilton; Susannah Evans (Symphony in the Flint Hills, 2010)
At first, it may be somewhat perplexing to put art and the rancher or cowboy in the same sentence. But, if you ask a rancher about his personal “gear,” he will readily show you his treasured tools: the favorite saddle, his boots, the weathered lariat, the bit, the spurs, the chaps, and the buckles. All these objects provide their value first through function, and second, through expression of personal style.
Keywords: cowboy; style; art; spurs; chaps; traditional; gear; accessories; past; modern; horsemen; cattle; rancher; materials; objects; craft; craftsman; saddle; leather hide; boots; bootmaking; rawhide; vintage